The Impact of Fuel Ownership on Intrastate Violence - Tim Wegenast (German Institute of Global and Area Studies (GIGA), 2013)
The impact of natural resources on intrastate violence has been increasingly analyzed in the peace and conflict literature. Surprisingly, little quantitative evidence has been gathered on the effects of the resource-ownership structure on internal violence. This paper uses a novel dataset on oil and natural gas property rights covering 40 countries during the period 1989-2010. The results of regression analyses employing logit models reveal that the curvilinear effect between hydrocarbon production and civil conflict onset - often found in previous studies - only applies to countries in which oil and gas production is mainly state controlled. The findings suggest that only state-owned hydrocarbons may entail peacebuying mechanisms such as specific clientelistic practices, patronage networks, welfare policies, and/or coercion. At the same time, it seems that greed and grievance are more pronounced whenever resources lie in the hands of the state. Exploring the within-country variation, further analyses reveal that divergent welfare spending patterns are likely to be one causal channel driving the relationship between resource ownership and internal violence.
Keywords: 300; natural resources; intrastate conflict; minor civil war; oil; gas; ownership structure; national oil companies